Zinc Oxide Defect Microstructure and Surface Chemistry Derived from Oxidation of Metallic Zinc. Thin Film Transistor and Sensoric Behaviour of ZnO Films and Rods. Issue 17 (4th February 2021) - Hoffmann, Rudolf C.; Sanctis, Shawn; Liedke, Maciej O.; Butterling, Maik; Wagner, Andreas; Njel, Christian; Schneider, Jörg J.
Abstract: Invited for the cover of this issue is Jörg J. Schneider and co‐workers at Technical University Darmstadt, Helmholtz‐Zentrum Dresden‐Rossendorf and KIT Karlsruhe. The image depicts the application of high energy generated electron/positron couples which are able to detect defects sites in semiconducting zinc oxide thin films. Read the full text of the article at 10.1002/chem.202004270 . Abstract : " We developed a seeding methodology for obtaining zinc oxide nanorods. It employs zinc oxide nanoparticles for nanorod growth using a molecular precursor onto the surface of crystalline semiconducting zinc oxide thin films. The obtained ZnO nanorods show a high UV sensitivity and the ZnO thin films a decent field effect transistor performance. Their defect characteristics were studied by positron annihilation spectroscopy ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 5422 ff. (DOI: 10.1002/chem.202004270 ).